The Role of Blockchain in Driving Supply Chain Transparency (Universitas Kristen Indonesia Toraja, 2023)
Blockchain technology has emerged as a transformative innovation for supply chain management. This study investigates its potential to enhance transparency, traceability, and efficiency across various industries. Through qualitative analysis of case studies, we reveal how blockchain improves consumer trust and reduces operational risks, while addressing its limitations such as scalability and adoption barriers.